Alteration and Vein Textures Associated with Gold Mineralization at the Bunikasih Area, Pangalengan, West Java - Subandrio, Andri S.; Basuki, N. I. (Geological Agency, 2010)
DOI: 10.17014/ijog.v5i4.108The Bunikasih vein system in the Pangalengan district of West Java is a low-sulfidation, adularia sericite epithermal gold deposit. It is hosted by Late Miocene andesitic volcanic and volcanoclastic rocks occurring in the south western margin of Malabar Volcano complex. Gold ore and alteration minerals related to deposition of gold in Bunikasih deposits superimposed on Late Tertiary-Quaternary andesitic formation that were altered and mineralized by some hydrothermal events. The veins consist almost entirely of quartz, with small amounts of adularia, bladed calcite, pyrite, and gold. Gold ore shoots are vertically restricted and are more continuous horizontally. The veins display complex and multi episodic filling with texture characteristics of open space precipitation such us colloform, lattice bladed, crustiform banding, vugs, breccia, and cockade and comb texture. The presence of bladed calcite and silica pseudomorph after bladed calcite suggests that the hydrothermal fluids boiled. In the Cibaliung section of the area, anomalous gold is related to veins trending northeast - southwest, milky quartz with dark grey to black manganese staining is found intermittently for a length of about 800m. The mineralized andesite ore bodies exhibit broad alteration patterns adjacent to mineralization, passing from fresh rock into anargillic, chlorite zone, and then sericite-silica close to mineralization. An argillic assemblage composed of kaolinite with fine-grained pyrite bulb is present in the upper portions and surrounding of the quartz vein system. The veins range from centimeter to meter in size. Of 24 vein samples collected, gold averages up to 0.3 grams per tone (